Penegakan Hukum terhadap Tindak Pidana Perjudian Toto Gelap - Natanail Sitepu; Isnaini Isnaini; Muhammad Citra Ramadhan (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
This study aims to analyze the legal rules regarding the crime of gambling to analyze what factors encourage the occurrence of illegal toto gambling crimes, especially in Deli Serdang Regency. The research method used is descriptive method, with a case approach and legislation, with interview data collection instruments and documentation studies, while the data analysis technique uses qualitative descriptive. The results of the study show that the legal regulation of lottery gambling is based on article 303 of the Criminal Code and article 303 bis and the UTE Law article 27 paragraph (2), with criminal threats in article 45 paragraph (2), as well as Law no. 7 of 1974 concerning Gambling Control in Article 1 that gambling in any form is a crime. The factors that encourage the occurrence of gambling crimes in Deli Serdang Regency are: the hope of getting a win, the influence of the environment, lottery gambling is easy for everyone to do, it doesn't take much time to do it, lottery clerks are available in many places, the development of information technology make it easier for players to send guesses for lottery gambling numbers, as well as weak supervision by the police. Law enforcement against lottery type gambling at the Lubuk Pakam District Court is still not firm.